Constitutional and legal mechanism of conducting foreign policy of the Czech Republic - Elena Aleksandrovna Kremyanskaya, Evgeniy Yakovlevich Pavlov, Anna Vladislavovna Shashkova,; Konstantin Anatolyevich Polovchenko, Yuri Ivanovich Leibo, (Opción, 2019)
The paper is concerned with the study of the organization and functioning of the constitutional and legal mechanism of conducting the foreign policyof the Czech Republic with use of statistical and comparative-legal methods. The authors begin their research with the historical surveyand pay attention to functional relationships of governmental authorities conferred with foreign policy powers. The paper ends up with the perspectives for further research. The authors believe that special consideration should be given to the aspect that remains beyond the scope of this paper, which is the mechanism of making foreign policy decisions in the Czech Republic.